2020
DOI: 10.2147/idr.s251490
|View full text |Cite
|
Sign up to set email alerts
|

<p>Molecular Investigations of Linezolid Resistance in Enterococci <em>OptrA</em> Variants from a Hospital in Shanghai</p>

Abstract: Purpose: The OptrA protein is a member of ATP-binding cassette (ABC) transporters, a transporter family which can confer resistance to oxazolidinone antibiotics by transferring plasmid. We aim to describe the distribution of optrA-harbored Enterococcus in Huashan hospital in 2017 and to address the effects of optrA mutations on the susceptibility of linezolid antibiotic drug. Methods: Linezolid-resistance-related genes were tested for Enterococcus by polymerase chain reaction (PCR) and then sequenced for amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
3
10
0
Order By: Relevance
“…are known to produce low-level resistance to aminoglycosides by limiting drug uptake, which is associated with the proteins involved in electron transport [48]. More so, the OptrA gene implicated in linezolid resistance was found in only one isolate (2SIL2) however, it was unexpressed as the isolate was susceptible to linezolid (Table 1 and S2) as reported in study in China were OptrA was found in eighteen linezolid non-resistant enterococci [49].…”
Section: Discussionmentioning
confidence: 98%
“…are known to produce low-level resistance to aminoglycosides by limiting drug uptake, which is associated with the proteins involved in electron transport [48]. More so, the OptrA gene implicated in linezolid resistance was found in only one isolate (2SIL2) however, it was unexpressed as the isolate was susceptible to linezolid (Table 1 and S2) as reported in study in China were OptrA was found in eighteen linezolid non-resistant enterococci [49].…”
Section: Discussionmentioning
confidence: 98%
“… 44 Furthermore, it is higher than strain isolated from Shanghai (0.5mg/L). 46 Despite the emergence of co-existence of optrA and poxtA worldwide, limited genetic context was identified and we hope to obtain more genomic data to explain whether there are other mechanisms or negative regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Acquisition of linezolid resistance is also associated to Cfr and Cfr-like methylases (in Enterococcus case cfr(B) and cfr(D) ) [ 192 , 203 , 204 , 206 , 207 , 208 , 209 , 210 , 211 ], ABC-F proteins optrA [ 197 , 199 , 201 , 212 , 213 ] and the previously mentioned PoxtA [ 192 , 200 , 204 ]. The optrA gene seems to be the most frequent mechanism of resistance to linezolid in E. faecalis [ 204 , 212 ].…”
Section: Antibiotic Resistancementioning
confidence: 99%